KAWASAN WISATA KAMPUNG KETUPAT DI KOTA BANJARMASIN - Ling, Mei; Muchamad, Bani Noor (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
Sungai Baru is a settlement of the home industry for ketupat, lontong, and nipah handicrafts which is traversed by the Martapura River, one of the biggest rivers in Banjarmasin City. However, the existence of this home industry has decreased which impacts the economic conditions of the residents. Therefore, Sungai Baru area has the potential to be used as a tourist area that can increase the existence of home industries of ketupat, lontong, and nipah handcrafts to maintain the Banjar culture. The main of the architectural problem for this study is the protrusion of the identity of the ketupat village which can increase the potential of the area. Through the concept of the Eco-Regionalism program with contextual architectural methods, it is hoped that the tourist area can highlight the characteristics of the Sungai Baru area as a ketupat village by paying attention to environmental and community aspects.